Patients infected with Mycobacterium africanum versus Mycobacterium tuberculosis possess distinct intestinal microbiota. - Sivaranjani Namasivayam; Bassirou Diarra; Seydou Diabate; Yeya Dit Sadio Sarro; Amadou Kone; Bourahima Kone; Mohamed Tolofoudie; Bocar Baya; Mahamane T Diakite; Ousmane Kodio; Keira Cohen; Jane Holl; et al. (Public Library of Science (PLoS), 2020)
BACKGROUND:Mycobacterium tuberculosis complex (MTBC), the causative agent of tuberculosis (TB), is composed of eight subspecies. TB in West Africa, in contrast to other geographical regions, is caused by Mycobacterium africanum (MAF) in addition to M. tuberculosis (MTB), with both infections presenting similar symptoms. Nevertheless, MAF is considered to be hypovirulent in comparison with MTB and less likely to progress to active disease. In this study, we asked whether MAF and MTB infected patients possess distinct intestinal microbiomes and characterized how these microbiota communities are affected by anti-tuberculosis therapy (ATT). Additionally, we assessed if the changes in microbiota composition following infection correlate with pathogen induced alterations in host blood-gene expression. METHODS:A longitudinal, clinical study of MAF infected, MTB infected patients assessed at diagnosis and two months after start of ATT, and healthy, endemic controls was conducted to compare compositions of the fecal microbiome as determined by 16S rRNA sequencing. A blood transcriptome analysis was also performed on a subset of subjects in each group by microarray and the results cross-compared with the same individual's microbiota composition. FINDINGS:MAF participants have distinct microbiomes compared with MTB patients, displaying decreased diversity and increases in Enterobacteriaceae with respect to healthy participants not observed in the latter patient group. Interestingly, this observed elevation in Enterobacteriaceae positively correlated with enhanced inflammatory gene expression in peripheral blood and was reversed after initiation of ATT. INTERPRETATION:Our findings indicate that MAF and MTB have distinct associations with the gut microbiome that may be reflective of the differential susceptibility of West Africans to these two co-endemic infections either as biomarkers or as a contributing determinant.